Understanding Intellectual Disability Inclusion in Nigeria's Public Administration: Challenges, Diagnosis, and Treatment - Paul Okudolo, Ikemefuna Taire; Ojakorotu, Victor (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
This study analyzes the intrinsic causes of disabled persons' marginalization from elite circles in Nigerian public administration organizations. Its foci among other things are to proffer measures for Nigeria's context of disabled persons' advancement into public bureaucracies' assembly of decision-makers, promote their topmost belongingness in public policy governance, offer ways to sustain disability-friendly public personnel promotion stratagem, propose means to realize public sector-friendly disability inclusivity. Political culture theory is espoused as the theoretical framework. The study parallels the qualitative methodology of a phenomenological inclination. Perceptions, views, and notions on how to promote disability-friendly policies, across all Nigerian public ministries, departments, and agencies (MDGs), toward facilitating upward mobility of disabled public administrators into directorate positions in the public services, derived from questionnaires, interviews, and correlated document analysis constituted data for the study. Content analysis approach guided by heuristic re-constructionism epistemology was adopted for analyzing data. Data from questionnaires were presented in quantitative content analysis. The study finds that there persist low political will towards domestication and implementation of globally agreed affirmative statutes for sustainable advancement of the education, talents, employment, promotion, and generally inclusion of disabled persons, particularly into the elite circle of Nigerian public bureaucracies. The finding mentioned above highlights the immanent variables that constitute major obstacles to the disabled public personnel belongingness as elite public administrators in determining the outputs and outcomes of public administration in Nigeria. It recommends, amongst others, prioritization of disabled persons' inclusion into the top staff echelon of public administration's MDGs across all the Nigerian tiers.